Advances in Tangible and Embodied Interaction for Virtual and Augmented Reality (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Virtual and augmented reality technology has seen tremendous progress in recent years, enabling novel and exciting ways to interact inside virtual environments. An interesting approach to interaction in VR and AR is the use of tangible user interfaces, which leverage on our natural understanding of the physical world and how our bodies move and interact with it, and on our learned capabilities to manipulate physical objects.For this Special Issue, we are interested in gathering research that bridges atoms and bits in virtual and augmented environments. Basic research papers that demonstrate new interaction technologies or techniques, descriptions of applications that use tangibles in VR/AR in any domain, and survey papers that can help structure and systematize current knowledge on this area are all suitable.